Configurative bases of the leniency program in the Peruvian legal system: with reference to the effective collaboration - Valverde Encarnación, Gianpierre (Universidad Nacional del Litoral, 2019)
This paper analyzes the figures of effective collaboration in the criminal field and the clemency program in order to identify common elements that contribute to a clear and predictable application of the second tool. It is evaluated the importance of the identity protection of the informer, as well as the incentives to be considered in the structure of said mechanisms.